Pedi-hub a mixed-use pedicab facility and living museum uplifting the sikad-sikad in Tabaco City through narrative approach and life cycle simulation - Bongalon, Christianne Clarisse (College of Architecture, University of the Philippines Diliman, 2025)
In an increasingly car-centric nation remains a cycling-centric city, Tabaco. Through its local pedicab, the sikad-sikad, it earned the title of being the “Pedicab Capital of the Philippines.” The sikad-sikad industry, while informal, is integral as a low-emission mode of transportation and a cultural-touristic asset of the locality. This status, however, is still inevitably being challenged by modernization and urbanization. The study conducted an in-depth exploration of the sikad-sikad’s role in the city by looking at its timeline of life. An examination and analysis of the present conditions of the sikad-sikad and its associated industries and sectors uncovered gaps and spaces of opportunities for innovative solutions. Through the product-service lifecycle approach, a comprehensive system that can ensure its longevity and role as a nexus of culture, livelihood, and transportation in Tabaco City was established. The Pedi-Hub is a mixed use pedicab facility and living museum that marries industry and tourism to facilitate the lifecycle process of the sikad-sikad. This development shall house the ‘Cycling Hub’ where spaces for fabrication, utilization, and disposal and reuse are provided and encouraged to interact. The integration of an indoor cycling experience throughout the building envelope explores the relationship between mobility and architecture and features Tabaco City’s cycling and greater culture and tourism through a moving, living museum. This project, ultimately, aims to uplift the pedicab and Tabaco community and imagines a deeper integration of sustainable low-emission cycling into our spaces in the face of modernization and urbanization.